2015
DOI: 10.1039/c5ra21903e
|View full text |Cite
|
Sign up to set email alerts
|

Significant enhancement of the electroactive β-phase of PVDF by incorporating hydrothermally synthesized copper oxide nanoparticles

Abstract: The influence of copper oxide nanoparticles on the polymorphism of PVDF is systematically investigated. Strong interfacial interactions between the negative nanoparticle surface and positive –CH2 dipoles of PVDF enhance the electroactive β-phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 37 publications
4
70
0
Order By: Relevance
“…Numerous studies have shown that the crystallization behaviour of the 9 polymer depends on specific interfacial interactions between the nucleating agents and polymer chains [45,[47][48][49][50][51]. Therefore, the nucleation effect of the nanofillers depends on the particle surface charge and surface area, concentration, dispersion, lattice matching, and processing conditions [47,52,53]. The presence of nanofillers was shown to reduce the nucleation energy barrier, enhancing the crystallization rate and the degree of crystallinity of the polymer [47].…”
Section: Methods For the Improvement Of The Piezoelectric Response Ofmentioning
confidence: 99%
“…Numerous studies have shown that the crystallization behaviour of the 9 polymer depends on specific interfacial interactions between the nucleating agents and polymer chains [45,[47][48][49][50][51]. Therefore, the nucleation effect of the nanofillers depends on the particle surface charge and surface area, concentration, dispersion, lattice matching, and processing conditions [47,52,53]. The presence of nanofillers was shown to reduce the nucleation energy barrier, enhancing the crystallization rate and the degree of crystallinity of the polymer [47].…”
Section: Methods For the Improvement Of The Piezoelectric Response Ofmentioning
confidence: 99%
“…15(d) indicated that T H was too high, for all the samples processed using temperature prole 2 (Part VI in ESI †). 42,43…”
Section: Effects Of Non-isothermal Crystallization and Scco 2 Processmentioning
confidence: 99%
“…Since the current rapid development of portable electronic devices such as smart watches, smart phones and wireless body sensors to satisfy increased lifestyle mobility, there has been an urgent need for novel dielectric materials with properties of flexibility, light weight and cost‐effectiveness . In comparison to the brittleness, high density and poor machinability of traditional ceramic dielectric materials, polymers with natural advantages of mechanical flexibility, light weight, low cost and good processability can take this responsibility …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In comparison to the brittleness, high density and poor machinability of traditional ceramic dielectric materials, polymers with natural advantages of mechanical flexibility, light weight, low cost and good processability can take this responsibility. [6][7][8][9][10][11] However, the intrinsic low dielectric constant of polymers limits their practical application markedly but a requirement for compatible properties of flexibility and high dielectric constant still impels researchers to test all sorts of strategies to overcome this fatal drawback of polymers. [12][13][14][15][16] The common way is by blending high dielectric ceramic powder into polymer, [17][18][19][20][21] while high ceramic loadings and poor compatibility between rigid filler and soft matrix dramatically degrade the mechanical properties of the composites, thus negating the original flexibility of the polymers and restricting their applications.…”
Section: Introductionmentioning
confidence: 99%